Investigation of conscious mindfulness levels of individuals doing sports in the context of fitness centers in terms of various variables - Turan Baskonus (ROL Spor Bilimleri Dergisi)
Athlete conscious mindfulness is defined as athletes being aware of their physical and mental states during their training and performance, and increasing their ability to focus and concentrate. Since this level of conscious awareness can directly affect sports performance, determining the awareness levels of individuals who do sports is important for both performance development and the efficiency of training processes. Based on this importance, the purpose of the research was determined as investigating the conscious awareness levels of individuals who do sports in fitness centers. The research was conducted with the voluntary participation of 295 people. A personal information form prepared by the researcher was used to collect personal data, and the Athlete Mindfulness Scale was used to collect athlete mindfulness data. In the analysis of the data, independent samples t-test, one-way analysis of variance (ANOVA), and Tukey test were used. In general, when the research results are examined, it is seen that gender, education level and time spent on sports are not factor variables on the conscious awareness levels of individuals who do sports in fitness centers; it is seen that the status of doing sports research and having a training program or not are factor variables. This finding indicates that implementing a training program and conducting sports research can increase attention, mindfulness and confidence. As a result, the higher conscious mindfulness levels of individuals who do sports research are an indication that learning about sports and doing research can deepen this process. The higher conscious mindfulness levels of individuals who have a training program reveal that doing regular and planned sports can increase conscious mindfulness.